KEWAJIBAN PERUSAHAAN PAILIT DALAM PENYELESAIAN HAK-HAK KARYAWAN DITINJAU DARI UNDANG UNDANG NO 37 TAHUN 2004 TENTANG KEPAILITAN DAN UNDANG UNDANG NO 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Devi Susanto; Hasnati Hasnati; Fahmi Fahmi (Fakultas Hukum Universitas Wahid Hasyim, 2020)
The Manpower Law and the Bankruptcy Law are both specifically regulating laws and regulations, so that in practice the priority principle cannot be used because the two laws have the same position. This of course results in a conflict of norms which creates legal uncertainty for workers in obtaining their rights. The formulation of the problem in this research is the Obligations of Bankrupt Companies in Settling Employee Rights in terms of Law No. 37 of 2004 concerning Bankruptcy and Law No. 13 of 2003 concerning Manpower, and the Legal Consequences of Bankruptcy Company Obligations in Settling Employee Rights in Review From Law No. 37 of 2004 concerning Bankruptcy and Law No. 13 of 2003 concerning Manpower. The method used is normative legal research. Sources of data consist of primary legal materials, secondary legal materials, and tertiary legal materials. In this study the data were analyzed qualitatively and in drawing conclusions, the authors applied a deductive thinking method. The conclusion in this study has answered the problems that arise, namely the Obligations of the Bankrupt Company in Resolving Employee Rights in terms of Law No. 37 of 2004 concerning Bankruptcy and Law No. 13 of 2003 concerning Manpower, the Company still has responsibilities that must be fulfilled to employees. , both before and after the bankruptcy declaration was passed. Prior to the issuance of the bankruptcy decision, the Company is responsible for paying the outstanding employee's wages and other rights in full before the Company loses its authority to manage and transfer its assets by the curator. Employees are entitled to severance pay, period of service pay, and compensation, in addition, employees are also entitled to wages payable before and after the bankruptcy decision. Based on Article 39 paragraph (2) Bankruptcy explains that since the date of pronouncement of the bankruptcy declaration, the wages payable before and after the pronouncement of bankruptcy constitute a debt of bankruptcy assets. This provision is then strengthened by other provisions, namely Article 95 paragraph (4) of the Manpower Law which states that when a company is declared bankrupt, the wages and other rights of the worker / laborer are a debt with payment precedence. Legal Consequences of Bankruptcy Company Jurnal Ilmiah Ilmu Hukum QISTIE Vol. 13 No. 2 November 2020 243 Obligations in Settling Employee Rights In terms of Law No. 37 of 2004 concerning Bankruptcy and Law No. 13 of 2003 concerning Manpower, the company represented by the board of directors still has the duty to assist in resolving bankruptcy assets at the request of the curator. This is done to achieve the aims and objectives of the Company for bankruptcy so that debts to creditors, including employees as preferred creditors, can be realized. Employees as Creditors who are privileged in this case depend heavily on the actions taken by the curator because employees do not have the authority to carry out the execution of material guarantees like those of the Separatist Creditors.